Study on a Low-Cost and Large-Scale Environmentally Adaptive Protocol Stack of Nuclear and Space Wireless Sensor Network Applications Under Gamma Radiation. (2nd January 2017) - Liu, Yu; Nishimura, Michael; Li, Liqian; Colins, Karen
Abstract : With the advancement of computer and communication technologies, wireless sensor networks (WSNs) are increasingly used in nuclear and space applications of radiation dose monitoring, earth observation, etc. In both cases, intensive radiation effects on electronic survivability are a concern. Gamma-ray damaging mechanisms in semiconductor devices are described as, and specifically linked to, semiconductor property changes in detectors, transistors, and integrated circuits. Radiation damage is cumulative and can result in the premature failure of WSN nodes. Thus, radiation-resistant electronics are commonly used for space and nuclear applications. However, these devices present a significant cost, especially when monitoring large areas. This paper focuses on studying a protocol stack that achieves an effective compromise in the cost and performance in a large-scale gamma radiation environment. The probability density function of a Weibull distribution is used to model failures of individual nodes in simulated WSNs. The distribution parameters are based on results of radiation-damage tests performed on semiconductor devices in the Gamma-220 facility ( 60 Co source) at the Canadian Nuclear Laboratories (CNL). The simulation of the protocol stack proposed in this paper through network simulator 2 (NS2) and the resulting performance analyses could provide useful design insights and considerations for nuclear and space applications. Our work is the first study on designing an environmentally adaptive protocol stack in a large-scale gamma radiation environment for nuclear and space applications.